Odontites linkii subsp. cyprius Ethanolic Extract Indicated In Vitro Anti-Acanthamoeba Effect - Chad Schou; Zeynep Kolören; Jandirk Sendker; Yiannis Sarigiannis; Aleksandar Jovanovic; Panagiotis Karanis (Microorganisms)
This study aims to investigate three endemic ethanolic leaf extracts from Cyprus for anti-Acanthamoeba activities: Odontites linkii subsp. cyprius (Boiss.) Bolliger, Ptilostemon chamaepeuce subsp. cyprius (Greuter) Chrtek & B. Slavík, and Quercus alnifolia Poech. Screening for radical scavenging activity, total phenolic content (TPC), and total flavonoid content (TFC) were performed by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABST) methods, Folin–Ciocalteu method, and aluminum chloride method, respectively. An antibacterial-susceptibility test (AST) was performed using a broth microdilution assay to estimate the minimum inhibitory concentration (MIC) using iodonitrotetrazolium chloride (INT). Trypan blue (0.5%) was used to assess in vitro anti-Acanthamoeba cell viability of the ethanolic leaf extracts after 24-, 48-, and 72-h exposure—screening of ethanolic leaf extracts with liquid chromatography–mass spectrometry (LC-MS) for known compounds with biological activity. The ethanolic leaf extract of Odontites linkii subsp. cyprius demonstrated the highest anti-Acanthamoeba activity, with an inhibitory concentration (IC50) of 7.02 mg/mL after 72 h. This extract also showed an in vitro minimum inhibitory concentration (MIC) of 0.625 mg/mL against Enterococcus faecalis, a common nosocomial pathogen. The LC-MS analysis revealed the presence of bioactive iridoid compounds in O. linkii subsp. cyprius, further highlighting its potential as a source for new drug compounds. The ethanolic extract of O. linkii subsp. cyprius demonstrated a dose-dependent and time-dependent anti-Acanthamoeba effect in vitro. This study is the first to report the presence of iridoid compounds and anti-Acanthamoeba activities in the ethanolic extract of O. linkii subsp. cyprius. These promising findings highlight the potential of plant extracts, particularly O. linkii subsp. cyprius, as a source for new drug compounds for Acanthamoeba infections.